Focusing and interiority (Journal of Parents and Teachers, 2023)
For a long time we have believed that mental activity is practically the only way to contact our innermost self. Nowadays, however, it is becoming increasingly evident that the body is a fundamental source for getting to know ourselves better. Focusing is a tool that helps us to become aware of what the body knows before the mind does.
Keywords: body; felt sensation; experience; listening; empathy